Deixis Analysis in First Chapter of The Rainbow Troops Novel: Ten New Students by Andrea Hirata - Lenggahing Asri Dwi Eko Saputri (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
One of the subjects that learn about language that can help human in using it is pragmatics. Pragmatics is the study of contextual meaning. Therefore, there must be a relationship between language and the context. The most obvious way to reflect the relationship between language and context is through deixis. Deixis is derived from the Greek word means pointing. There is no a language event without deixis or without any deictic expressions. A language event without such terms could not serve the communicative needs of its users anything like as well as a real human language. In this mini research, I chose to analyze an Indonesian novel entitled “Laskar Pelangi” (The Rainbow Troops) written by Andrea Hirata which had been translated in English by Angie Kilbane because in a novel there must be a context that surrounds the language. Moreover, in the context and the language there must be deixis between them to make the novel cohesive, coherent and acceptable for the reader. Therefore, a novel is a good material to be analyzed in finding the deixis. Based on some elaborations above, I can conclude that the use of deixis in The Rainbow Troops novel written by Andrea Hirata in 2009 need to be analyzed in the term of what types of deixis used in the novel and what the dominant type of deixes used in the novel. Keywords:pragmatics; deixis; Indonesian novel